Global formulations of Lagrangian and Hamiltonian dynamics on manifolds : a geometric approach to modeling and analysis /: a geometric approach to modeling and analysis. ([2018]) - Lee, Taeyoung; Leok, Melvin; McClamroch, N. H (N. Harris)
No abstract available